EFISIENSI PEMASARAN KOPI ARABIKA DI KECAMATAN KAYU ARO KABUPATEN KERINCI - Sri Fitriya (Jurnal Bina Bangsa Ekonomika, 2024)
Based on research result from marketing channel I to marketing channel VI in Harjokuncaran Village, share farmer price in marketing channel I is 94,54 % with total margin Rp1557,-, share farmer price in marketing channel II is 96,68 % with total margin Rp375,-, share farmer price in marketing channel III is 95,37 % with total margin Rp1307,- , share farmer price in marketing channel IV is 94,74 % with total margin Rp1500,- share farmer price in marketing channel V is 93,10 % with total margin Rp 2000,- and marketing channel VI has total margin Rp700,- where sortation cost incured by farmers is called margin because the farmers as marketing institutions thar direcly sell their coffee to consumer or Agroindustry without through the marketing institution of middleman or distributor. The price efficiency approach is calculated based on the marketing institutions for each marketing channel. According to the research result, the fuction transportation by every marketing institutions have been efficient. Because price difference bigger than transportation cost. The operational efficiency approach is calculated useing standart capacity in each activity that is transportation used by marketing institutions. Based on research result that middlemand in marketing channel I and middleman in marketing channel IV have not effiicient because capacity average under normal capacity that are 87,50 % < 100 % and 95 % < 100 %. While distributor in marketing channel I and channel II have been said efficient becaude the avegare capacity is over capacity that is 245,83%. Factors affected marketing margin of Arabika coffee in Harjokuncaran Village are farmer distance with marketing institution (X1), farming length (X2), farmer price (X3), farmer age (X4), and farmer education (X5) simultaneously. Partially, farmer distance (X1) had negatively affected to marketing margin with coefficient value is 34,28811 and farmer price had negatively affected to marketing margin with coefficient value is 0,18988839. While farming length (X2), farmer age (X4), and farmer education (X5) have not affected to marketing margin. Suggestion for farmers, should sell coffee directly to distributor Dampit so that get a high selling price. So, the role of goverment is needed to help farmers do their own sorting and do picking quality coffee beans